2005
DOI: 10.1508/cytologia.70.225
|View full text |Cite
|
Sign up to set email alerts
|

Relative Genotoxic Effects of Cypermethrin, Alphamethrin and Fenvalerate on the Root Meristems of Allium cepa

Abstract: SummaryThe present investigation deals with the effects of 3 synthetic pyrethroid insecticides viz., Cypermethrin, Alphamethrin and Fenvalerate on the mitotic activity and mitotic chromosomes in the root meristems of Allium cepa. Root meristems were exposed to 4 different concentrations of each test compound for 1 h pulse treatment and allowed to different recovery periods.Cytological analyses revealed that the test compounds elicited varying degrees of cytotoxic, turbagenic (toxicity to spindle) and clastogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
4
0

Year Published

2007
2007
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 20 publications
0
4
0
Order By: Relevance
“…Cypermethrin and alphamethrin were reported to elicit varying degrees of cytotoxic, turbagenic (toxicity to spindle) and clastogenic effects but generally more turbagenic and weak clastogenic (Rao et al, 2005). However, Asita and Makhalemele (2008) reported that alpha-thrin (active ingredient of alpha-cypermethrin) was only cytotoxic but not genotoxic at various concentrations in treated A. cepa.…”
Section: Resultsmentioning
confidence: 99%
“…Cypermethrin and alphamethrin were reported to elicit varying degrees of cytotoxic, turbagenic (toxicity to spindle) and clastogenic effects but generally more turbagenic and weak clastogenic (Rao et al, 2005). However, Asita and Makhalemele (2008) reported that alpha-thrin (active ingredient of alpha-cypermethrin) was only cytotoxic but not genotoxic at various concentrations in treated A. cepa.…”
Section: Resultsmentioning
confidence: 99%
“…Micronuclei are the results of acentric fragments, lagging chromosomes, chromosome breakage or whole chromosomes that fail to incorporate into one of the daughter nuclei during telophase of mitotic cells (Albertini et al 2000; Fenech 2007). It is suggested that loss of genetic material reveal genomic instability (Barale et al 1998) and may reveal cell death (Luzhna and Kovalchuk 2013).aberrations, which is in agreement withRao et al, (2005), while opposes Asita and Makhalemele (2008), who reported cypermethrin (Alpha-thrin) as cytotoxic, but not genotoxic at various concentrations. However, malathion is more genotoxic than cypermethrin.…”
mentioning
confidence: 55%
“…(Rao et al 2005; Yekeen et al 2013; Dizdari and Kopliku 2013). Malathion toxicity to plants was clearly determined (Adam et al 1990; Bianchi et al 2015; Garza-León et al 2017).…”
mentioning
confidence: 99%
“…According to Rao et al (2005), high quantities of cypermethrin cause chromosomal aberrations in metaphase and chromosome bridge creation in anaphase. In this research, sticky chromosomes (Figure 6); chromosome bridge (Figure 7); chromosome agglutination (Figure 8); disrupted metaphase (Figure 9), and disturbed anaphase were identified as chromosomal aberrations (Figure 10).…”
Section: Chromosomal Aberrationsmentioning
confidence: 99%